A method to improve the storage life of solid-state batteries
By rapidly heating up the solid-state battery and dehydrating it for short-term insulation before or after assembly, the performance degradation caused by water absorption by solid-state batteries is solved, and the storage life and circulation performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202210223709.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-09
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-03-09
AI Technical Summary
During the storage process, solid-state batteries have a decrease in conductivity and stability due to water absorption, and narrow the electrochemical window, which in turn reduces the battery capacity and poor cycle performance, affecting the storage life.
Using the dehydration treatment steps before or after assembly, the moisture in the positive electrode sheet and solid battery is removed by rapid heating and short-term insulation, and the heating and cooling rates are controlled at 15-20℃/min and 10-15℃/min. During the period, ensure that the components are dehydrated within the range of 100-170°C and 120-170°C.
It effectively reduces the moisture content of the battery cell in the packaging bag, prevents the oxidation of the positive electrode active substance, prevents the diffusion of moisture to the solid electrolyte, improves the storage performance and circulation performance of the solid battery, and extends the storage life.
Smart Images

Figure CN114824491B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a method for improving the storage life of solid-state batteries. Background Art
[0002] In recent years, solid-state batteries have received extensive attention and attention from researchers at home and abroad, and have developed rapidly. Solid-state batteries use non-flammable solid electrolytes to replace flammable organic liquid electrolytes, which greatly improves the safety of the battery system. At the same time, they can better adapt to high-energy positive and negative electrodes and reduce the weight of the system, achieving a simultaneous increase in energy density. Among various new battery systems, solid-state batteries are the next-generation technology closest to industrialization, which has become a consensus in the industry and the scientific community.
[0003] Solid-state batteries use solid electrolytes to replace traditional liquid electrolyte components. Currently, inorganic solid electrolytes are commonly used, such as sulfide electrolytes, oxide electrolytes, and halide electrolytes. However, these solid electrolytes are generally sensitive to water and easily absorb water.
[0004] Based on the above characteristics of solid electrolytes, even if the water in the solid electrolyte material can be completely removed by high-temperature sintering and other methods during the preparation process, the various links involved in the preparation process of each component (such as: solid-state battery positive electrode, solid-state battery negative electrode, solid electrolyte layer) with the addition of solid electrolytes (such as: mixing, homogenization, coating, rolling, battery assembly) will inevitably be exposed to trace amounts of water present in the atmosphere, adsorbed on the equipment, and adsorbed on various auxiliary materials and materials. These trace amounts of water will gradually diffuse into the solid electrolyte with stronger water-sucking ability during the storage of the battery. The solid electrolyte after absorbing water will show a decrease in conductivity, stability, and a narrowing of the electrochemical window, which will reduce the capacity of the stored solid-state battery compared to the freshly made battery and deteriorate the cycle performance. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defects of solid-state batteries in the prior art that the battery capacity is reduced and the cycle performance is deteriorated during storage, thereby providing a method for improving the storage life of solid-state batteries.
[0006] The present invention provides a method for improving the storage life of a solid-state battery, characterized in that the method for improving the storage life of a solid-state battery comprises a dehydration treatment step before assembly or a dehydration treatment step after assembly;
[0007] The dehydration treatment before assembly includes heating the positive electrode sheet from room temperature to a predetermined temperature X1, keeping it at the predetermined temperature X1 for T1 time, and cooling it to below 80°C; 100°C≤X1≤170°C, 1min≤T1≤20min, heating rate ≥15°C / min, cooling rate ≥10°C / min;
[0008] The dehydration treatment after assembly includes heating the solid-state battery from room temperature to a predetermined temperature X2, keeping it at the predetermined temperature X2 for T2 time, and cooling it to below 80°C; 120°C≤X2≤170°C, 10min≤T2≤20min, heating rate ≥15°C / min, cooling rate ≥10°C / min.
[0009] Furthermore, the temperature rise rate of the positive electrode sheet is 15-20°C / min; the temperature drop rate is 10-15°C / min; and / or, the temperature rise rate of the solid-state battery is 15-20°C / min; the temperature drop rate is 10-15°C / min.
[0010] The dehydration step before assembly also includes: a step of dehydrating the negative electrode sheet and / or the solid electrolyte membrane. Preferably, the negative electrode sheet and the solid electrolyte membrane are heated from room temperature to a predetermined temperature X3, kept at the predetermined temperature X3 for T3 time, cooled to room temperature and set aside; 120℃≤X3≤330℃, 10min≤T3≤40min; more preferably, the heating rate of the negative electrode sheet and the solid electrolyte membrane is ≥10℃ / min, and the cooling rate is ≥5℃ / min.
[0011] For example, the heating rate of the negative electrode sheet and the solid electrolyte membrane is 10-20°C / min; the cooling rate is 5-15°C / min.
[0012] The present invention also provides a method for preparing a solid-state battery, including any of the above-mentioned methods for improving the storage life of a solid-state battery, and also including the preparation of a positive electrode sheet, the preparation of a negative electrode sheet and the preparation of a solid electrolyte membrane.
[0013] Furthermore, the preparation method of the positive electrode sheet comprises the following steps: mixing a binder, a positive electrode active material, a solid electrolyte and conductive carbon, rolling to obtain a positive electrode sheet, and pressing the positive electrode sheet with a current collector to obtain a positive electrode sheet;
[0014] The preparation method of the negative electrode sheet comprises the following steps: mixing a binder, a negative electrode active material, a solid electrolyte and a conductive carbon, rolling and pressing to obtain a negative electrode sheet, and pressing the negative electrode sheet and a current collector to obtain a negative electrode sheet;
[0015] The method for preparing the solid electrolyte membrane comprises the following steps: mixing the solid electrolyte with the binder, and rolling to obtain the solid electrolyte membrane.
[0016] Furthermore, the binder is selected from at least one of polyvinylidene fluoride, polyethylene oxide and polytetrafluoroethylene, preferably polytetrafluoroethylene.
[0017] Further, in the preparation method of the positive electrode sheet, the mass ratio of the binder, the positive electrode active material, the conductive carbon and the solid electrolyte is 0.2-5: 50-90: 0.05-4: 1-50; and / or, in the preparation method of the negative electrode sheet, the mass ratio of the binder, the negative electrode active material, the solid electrolyte and the conductive carbon is 0.2-5: 50-90: 0.05-4: 1-50; and / or, in the preparation of the solid electrolyte membrane, the mass ratio of the binder to the solid electrolyte is 0.1-10: 90-99.9; and / or, the thickness of the positive electrode sheet is 50-120 microns; and / or, the thickness of the solid electrolyte membrane is 20-200 microns; and / or, the thickness of the negative electrode sheet is 60-170 microns.
[0018] Furthermore, the peel strength of the positive electrode sheet and / or the negative electrode sheet is 30-80 mN / mm.
[0019] The test method for peel strength is as follows: stick the pressure-sensitive adhesive 3M-VHB double-sided adhesive on the surface of the positive electrode or the negative electrode, and stick the other side on the stainless steel plate. Fix the stainless steel plate and the current collector on the fixture of the tensile tester respectively, and then perform a 180-degree peel test at a speed of 10mm / min and a load of 10N.
[0020] Furthermore, in the preparation of the positive electrode sheet and / or the preparation of the negative electrode sheet and / or the preparation of the electrolyte membrane, the mixing method is at least one of grinding, ball milling, stirring, oscillation and ultrasound; and / or the rolling temperature is 40-220°C.
[0021] During the preparation of the positive electrode sheet, the negative electrode sheet or the electrolyte membrane, roller pressing may be performed within a conventional pressure range, for example, a pressure range of 20-1000 kg.
[0022] Further, the negative electrode active material is selected from at least one of graphite, silicon dioxide, silicon, lithium carbonate, and lithium titanate; and / or, the solid electrolyte is selected from at least one of sulfide electrolytes, halogen electrolytes, and oxide electrolytes; and / or, the positive electrode active material is selected from at least one of nickel cobalt manganese materials, nickel manganese lithium oxide materials, nickel lithium oxide materials, lithium cobalt oxide materials, nickel cobalt lithium oxide materials, and nickel manganese cobalt lithium oxide materials; and / or, the conductive carbon is selected from at least one of carbon black, acetylene black, carbon nanotubes, and graphene.
[0023] The positive electrode active material includes LiCoO 2 、LiNiO 2 、LiFePO 4 、LiNi 0.5 Mn0.5 O 2 、Li(NiCoMn) 1 / 3 O 2 , LiNi 1-x-y Co x Mn y O 2 , LiNi 1-x-y Co x Al y O 2 and LiMn 2 O 4 One or a combination of at least two of the following, wherein 0<x<1. LiNi 1-x-y Co x Mn y O 2 Materials such as LiNi 0.6 Co 0.2 Mn 0.2 O 2 、LiNi 0.8 Co 0.1 Mn 0.1 O 2 、LiNi 0.5 Co 0.2 Mn 0.3 O 2 .LiNi 1-x-y Co x Al y O 2 Materials such as LiNi 0.5 Co 0.2 Al 0.3 O 2 .
[0024] The sulfide electrolyte may be:
[0025] Li 7-x-2y PS 6-x-y Z x , wherein 0.7<x<1.8, 0≤y<-0.25x+0.5, and Z can be one or more of F, Cl, Br, and I.
[0026] The halide electrolyte can be Li 3-x M 1-x N x X 6 , wherein X can be one or more of F, Cl, Br, and I. M and N can be one of Sc, Y, Zr, Hf, Ga, In, La, Ce, Pr, Nd, Pm, Sm, Eu, Ga, La, Dy, H0, Er, Tm, Yb, and Lu, respectively, wherein 0≤x≤1.
[0027] The present invention also provides a solid-state battery prepared by any of the above-mentioned preparation methods.
[0028] The solid-state battery comprises a positive electrode sheet, a positive electrode current collector, a negative electrode sheet, a negative electrode current collector, and a solid electrolyte membrane.
[0029] The study found that the water in the battery cell before packaging mainly exists in two forms: one is free water, which is mainly the water adsorbed on the battery components during the preparation process. This part of water is relatively easy to remove and can be removed above the boiling point of water 100 degrees Celsius; the other part is bound water, which is mainly formed after free water contacts the solid electrolyte, namely M + xH 2 0 (M is solid electrolyte, x is the amount of bound water, generally 0.1<x<3), this part of water is difficult to remove, generally requires ≥160℃. However, using high temperature to dry the battery cell for a long time will cause the positive electrode active material (especially the high nickel ternary positive electrode) to lose oxygen, which will cause the collapse of the positive electrode active material structure and affect the performance of the battery.
[0030] The solid-state battery of the present invention can be assembled and packaged by using a positive electrode sheet, a positive current collector, a negative electrode sheet, a negative current collector, and a solid electrolyte membrane in an existing conventional manner. The obtained solid-state battery has a schematic diagram of a cell structure as shown in Figure 1 or Figure 2 .
[0031] like Figure 1 As shown, the battery cell structure includes a negative electrode collector 1, a negative electrode plate 2, a solid electrolyte membrane 3, a positive electrode plate 4 and a positive electrode collector 5 which are stacked in sequence, wherein the negative electrode collector and the negative electrode plate constitute the negative electrode plate; the positive electrode collector and the positive electrode plate constitute the positive electrode plate.
[0032] like Figure 2 As shown, the battery cell structure includes a positive electrode sheet and a negative electrode sheet; the positive electrode sheet includes a positive electrode collector 5 and a positive electrode sheet 4, a solid electrolyte membrane 3 is arranged between the positive electrode sheet and the negative electrode sheet, and one side surface of the solid electrolyte membrane 3 includes a recessed area adapted to the positive electrode sheet and a plane area enclosing the recessed area, the plane area is connected to one side of the positive electrode collector, the positive electrode sheet is located in the recessed area, and the two side surfaces of the positive electrode sheet are respectively connected to the positive electrode collector and the solid electrolyte membrane; the negative electrode sheet includes a negative electrode collector and a negative electrode sheet; the negative electrode sheet is connected to the other side of the solid electrolyte membrane. This battery cell structure can improve the safety performance, yield, cycle performance and manufacturing efficiency of all-solid-state batteries. In this embodiment, the cross-sectional area of the positive electrode sheet is 9 / 10 to 19 / 20 of the cross-sectional area of the positive electrode collector, for example, 9 / 10 in the following embodiment 3 of the present invention.
[0033] The technical solution of the present invention has the following advantages:
[0034] 1. The method for improving the storage life of a solid-state battery provided by the present invention comprises a dehydration step before assembly or a dehydration step after assembly, wherein the positive electrode sheet is heated to 100-170°C at a heating rate of ≥15°C / min, kept warm for 1-20 minutes, and then cooled at a cooling rate of ≥10°C / min, or the solid-state battery is heated to 120-170°C at a heating rate of ≥15°C / min, kept warm for 10-20 minutes, and then cooled at a cooling rate of ≥10°C / min. The above procedure can be used to achieve "rapid heating and short-term heat preservation" of the positive electrode sheet or the solid-state battery as a whole, effectively remove free water and bound water in the positive electrode sheet, effectively reduce the water content of the battery cell in the packaging bag, and prevent oxidation of the positive electrode active material, and prevent the storage performance from being reduced due to the diffusion of water into the solid electrolyte.
[0035] 2. The method for improving the storage life of solid-state batteries provided by the present invention also includes the step of dehydrating the negative electrode sheet and / or the solid electrolyte membrane. Preferably, the negative electrode sheet and the solid electrolyte membrane are heated from room temperature to a predetermined temperature X3, kept at the predetermined temperature X3 for T3 time, and cooled to room temperature for standby use; 120℃≤X3≤330℃, 10min≤T3≤40min; the moisture of the solid-state battery can be better removed.
[0036] In a more preferred technical solution, the preferred dehydration temperature of the positive electrode sheet is 110°C to 160°C; the preferred dehydration temperature of the solid electrolyte membrane and the negative electrode sheet is 160°C to 260°C.
[0037] 3. The method for improving the storage life of solid-state batteries provided by the present invention, before being processed by the steps of the present invention, the moisture content of each component in the solid-state battery is tested as follows: the moisture content of the positive electrode sheet> a, the moisture content of the solid electrolyte layer> 1 / 6a, the moisture content of the negative electrode sheet> 2 / 3a; after being processed according to the method of the present invention, the moisture content of each component is tested, and the moisture content of each component is <1 / 10a. The value range of a is 100-300ppm (ppm means one part per million).
[0038] 4. The preparation method of the solid-state battery provided by the present invention uses at least one of polyvinylidene fluoride, polyethylene oxide and polytetrafluoroethylene as a binder, preferably polytetrafluoroethylene, and no solvent is added. After polytetrafluoroethylene is mixed with other positive or negative electrode raw materials by mechanical mixing, the polytetrafluoroethylene powder is elongated, thinned, and filamentized by utilizing the characteristic that polytetrafluoroethylene can be filamentized under the action of external shear force. After filamentization, the polytetrafluoroethylene powder has stickiness and can bond the above-mentioned mixed powder together. After filamentization, polytetrafluoroethylene can bond other raw materials together, and the above-mentioned bonded body is rolled to achieve the purpose of thinning each layer and uniforming the thickness. After rolling, it is pressed together with the current collector by rolling again to form a complete pole piece.
[0039] 5. The preparation method of the solid-state battery provided by the present invention controls the peel strength of the positive electrode sheet and / or the negative electrode sheet to 30-80 mN / mm; so that the electrode sheet can fit well with the current collector, and prevent the electrode sheet and the current collector from peeling off from each other due to the expansion and contraction of the active material during the cycle, thereby further improving the cycle performance and specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 is a schematic structural diagram of a solid-state battery in Example 1 of the present invention;
[0042] Figure 2 is a schematic structural diagram of a solid-state battery in Example 3 of the present invention;
[0043] Figure 3 is a graph showing the relationship between the number of cycles and the first discharge specific capacity of the solid-state battery that has not been left to stand for 120 days in Example 1 of the present invention;
[0044] Figure 4 is a graph showing the relationship between the number of cycles and the first discharge specific capacity of the solid-state battery that has not been left to stand for 120 days in Example 2 of the present invention;
[0045] Reference numerals:
[0046] 1. Negative electrode current collector; 2. Negative electrode plate; 3. Solid electrolyte membrane; 4. Positive electrode plate; 5. Positive electrode current collector. DETAILED DESCRIPTION
[0047] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the guidance of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0048] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.
[0049] Example 1
[0050] This embodiment provides a method for preparing a solid-state battery, comprising the following steps:
[0051] (1) Preparation of positive electrode
[0052] Composition, based on the total mass of the positive electrode sheet being 100%, polytetrafluoroethylene powder accounts for 3wt%, lithium nickel cobalt manganese oxide (molecular formula: LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) accounts for 65wt%, conductive carbon (VGCF, vapor-grown carbon fiber) accounts for 2wt%, and sulfide electrolyte Li 6 PS 5 Cl accounts for 30wt%.
[0053] Put lithium nickel cobalt manganese oxide, solid electrolyte and conductive carbon into a blender and mix them evenly, and disperse the different particles through mechanical stirring. Then mix polytetrafluoroethylene powder with the above powders and mix them evenly through a blender.
[0054] The mixed powder was placed in a high-speed mixer with paddles and mixed at 800 rpm for 20 minutes. The mixed material was then placed in a roller press and hot rolled at 100°C to form a self-supporting positive electrode sheet without a current collector, with a thickness of 60 microns. The above-mentioned electrode sheet was then rolled together with the positive current collector (aluminum foil, thickness 20 microns) to form a complete solid-state battery positive electrode sheet with a peel strength of 52 mN / mm.
[0055] (2) Preparation of negative electrode sheet
[0056] Composition, based on the total mass of the negative electrode sheet being 100%, polytetrafluoroethylene powder accounts for 3wt%, lithium titanate accounts for 60wt%, conductive carbon accounts for 3wt%, and halide electrolyte Li 3 InCl 6 , accounting for 34wt%.
[0057] The negative electrode active material lithium titanate, solid electrolyte, and conductive carbon are put into a blender and mixed evenly, and different particles are dispersed by mechanical stirring. Then, polytetrafluoroethylene powder is mixed with the above powders and mixed evenly by a blender.
[0058] The mixed powder was placed in a high-speed mixer with paddles and mixed at 800 rpm for 20 minutes. The mixed material was then placed in a roller press and hot rolled at 100°C to form a self-supporting negative electrode sheet without a current collector, with a thickness of 90 microns. The above-mentioned electrode sheet was then rolled together with the negative current collector aluminum foil (thickness 20 microns) to form a complete solid-state battery negative electrode sheet with a peel strength of 47mN / mm.
[0059] (3) Preparation of solid electrolyte membrane
[0060] Composition, based on the total mass of the solid electrolyte being 100wt%, polytetrafluoroethylene powder accounts for 3wt%, and halide electrolyte Li is used 3 ScCl 6 , accounting for 97wt%.
[0061] The polytetrafluoroethylene powder and the solid electrolyte are mixed together and mixed evenly by a blender.
[0062] The mixed powder was placed in a high-speed mixer with paddles and mixed at 800 rpm for 20 minutes. The mixed material was then placed in a roller press and hot rolled at 100°C to form a self-supporting solid electrolyte membrane with a thickness of 40 microns.
[0063] (4) Dehydration
[0064] The solid-state battery positive electrode sheet was heated from room temperature to 150°C at a heating rate of 15°C / min, then kept at 150°C for dehydration for 10 minutes, and then cooled to room temperature at a rate of 10°C / min for standby use;
[0065] The solid electrolyte membrane and the solid battery negative electrode were subjected to the following dehydration treatment: the temperature was raised from room temperature to 230°C at a heating rate of 10°C / min, then kept at 230°C for dehydration for 20 minutes, and then cooled to room temperature at a rate of 5°C / min for standby use.
[0066] (5) Assembly and packaging of components
[0067] The dehydrated solid-state battery positive electrode sheet, solid electrolyte membrane, and solid-state battery negative electrode sheet are rolled together to obtain a battery cell, such as Figure 1 The combined battery cell is packaged in an aluminum-plastic film packaging bag to produce a solid-state battery.
[0068] Example 2
[0069] This embodiment provides a method for preparing a solid-state battery, comprising the following steps:
[0070] The positive electrode sheet, negative electrode sheet and solid electrolyte membrane are prepared according to the formulation and process methods of steps (1) to (3) of Example 1, and then the components are assembled and packaged according to the method of step (5) of Example 1, and the packaged solid-state battery is dehydrated.
[0071] The solid-state battery was heated from room temperature to 160°C at a heating rate of 15°C / min, then kept at 160°C for dehydration for 10 minutes, and then cooled to room temperature at a rate of 10°C / min.
[0072] Example 3
[0073] This embodiment provides a method for preparing a solid-state battery, comprising the following steps:
[0074] (1) Preparation of positive electrode
[0075] Composition, based on the total mass of the positive electrode sheet being 100%, polytetrafluoroethylene powder accounts for 5wt%, lithium nickel cobalt manganese oxide (molecular formula: LiNi 0.8 Co 0.1 Mn 0.1 O 2 ) accounts for 70wt%, conductive carbon black accounts for 0.1wt%, and sulfide electrolyte Li 6 PS 5 Br accounts for 24.9wt%.
[0076] Put lithium nickel cobalt manganese oxide, solid electrolyte and conductive carbon into a blender and mix them evenly, and disperse the different particles through mechanical stirring. Then mix polytetrafluoroethylene powder with the above powders and mix them evenly through a blender.
[0077] The mixed powder was placed in a high-speed mixer with paddles and mixed at 800 rpm for 20 minutes. The mixed material was then placed in a roller press and hot rolled at 80°C to form a self-supporting positive electrode sheet without a current collector, with a thickness of 100 microns. The above-mentioned electrode sheet was then rolled together with the positive current collector aluminum foil (thickness 20 microns) to form a complete solid-state battery positive electrode sheet with a peel strength of 73mN / mm.
[0078] (2) Preparation of negative electrode sheet
[0079] Composition, based on the total mass of the negative electrode sheet being 100%, polytetrafluoroethylene powder accounts for 5wt%, lithium titanate accounts for 65wt%, conductive carbon black accounts for 1.1wt%, and the halide electrolyte Li 3 YC 6 (Preparation method: LiCl and YCl 3 After mixing in a molar ratio of 3:1, a high-energy ball mill was used for ball milling at 400 rpm for 24 h, and then calcined at 300° C. for 6 h. ), the halide electrolyte accounted for 28.9 wt%.
[0080] Put lithium titanate, solid electrolyte and conductive carbon into a blender and mix them evenly, and disperse the different particles through mechanical stirring. Then mix polytetrafluoroethylene powder with the above powders and mix them evenly through a blender.
[0081] The mixed powder was placed in a high-speed mixer with paddles and mixed at 800 rpm for 20 minutes. The mixed material was then placed in a roller press and hot rolled at 80°C to form a self-supporting negative electrode sheet without a current collector, with a thickness of 140 microns. The above-mentioned sheet was then rolled together with the negative current collector aluminum foil (thickness 20 microns) to form a complete solid-state battery negative electrode sheet with a peel strength of 71 mN / mm.
[0082] (3) Preparation of solid electrolyte membrane
[0083] Composition, based on the total mass of the solid electrolyte being 100wt%, polytetrafluoroethylene powder accounts for 0.5wt%, and halide electrolyte Li is used 3 ScCl 6 (Preparation method: LiCl and ScCl 3 After mixing in a molar ratio of 3:1, a high-energy ball mill was used for ball milling at 360 rpm for 24 h, and then calcined at 350° C. for 8 h. ), the halide electrolyte accounted for 99.5 wt%.
[0084] The polytetrafluoroethylene powder and the solid electrolyte are mixed together and mixed evenly by a blender.
[0085] The mixed powder was placed in a high-speed mixer with paddles and mixed at 800 rpm for 20 minutes. The mixed material was then placed in a roller press and hot rolled at 80°C to form a self-supporting solid electrolyte membrane with a thickness of 80 microns.
[0086] (4) Dehydration
[0087] The solid-state battery positive electrode sheet is heated from room temperature to 100°C at a heating rate of 15°C / min, then kept at 100°C for dehydration for 20 minutes, and then cooled to room temperature at a rate of 10°C / min for standby use;
[0088] The solid electrolyte membrane and the solid battery negative electrode were heated from room temperature to 270°C at a heating rate of 10°C / min, then kept at 270°C for dehydration for 10 min, and then cooled to room temperature at a rate of 5°C / min for use.
[0089] (5) Assembly and packaging of components
[0090] The dehydrated solid-state battery positive electrode sheet, solid electrolyte membrane, and solid-state battery negative electrode sheet are rolled together to obtain a battery cell, such as Figure 2 The combined battery cell is packaged in an aluminum-plastic film packaging bag to produce a solid-state battery.
[0091] Example 4
[0092] This embodiment provides a method for preparing a solid-state battery, comprising the following steps:
[0093] (1) Preparation of positive electrode
[0094] Composition, based on the total mass of the positive electrode sheet being 100%, polytetrafluoroethylene powder accounts for 0.2wt%, lithium nickel cobalt manganese oxide (molecular formula: LiNi 0.8 Co 0.1 Mn 0.1 O 2 , accounting for 50wt%, conductive carbon black accounting for 4wt%, using sulfide electrolyte Li 6 PS 5 Br(LiBr、P 2 S 5 , Li 2 S was mixed in a molar ratio of 1:0.5:2.5, ball milled at 340 rpm for 26 h using a high-energy ball mill, and then sintered at 500 °C for 24 h. ), the sulfide electrolyte accounted for 45.8 wt%.
[0095] The positive electrode active material, solid electrolyte and conductive carbon are put into a blender and mixed evenly, and the different particles are dispersed by mechanical stirring. Then the polytetrafluoroethylene powder is mixed with the above powders and mixed evenly by a blender.
[0096] The mixed powder was placed in a high-speed mixer with paddles and mixed at 800 rpm for 20 minutes. The mixed material was then placed in a roller press and hot rolled at 100°C to form a self-supporting positive electrode sheet without a current collector, with a thickness of 50 microns. The above-mentioned electrode sheet was then rolled together with the positive current collector aluminum foil (thickness 20 microns) to form a complete solid-state battery positive electrode sheet with a peel strength of 35 mN / mm.
[0097] (2) Preparation of negative electrode sheet
[0098] Composition, based on the total mass of the negative electrode sheet being 100%, polytetrafluoroethylene powder accounts for 0.2wt%, lithium titanate accounts for 50wt%, conductive carbon black accounts for 4wt%, and halide electrolyte Li 2.4 Y 0.4 Zr 0.6 Cl 6 (LiCl, YCl 3 With ZrCl 4 After mixing in a molar ratio of 2.4:0.4:0.6, the mixture was ball-milled at 300 rpm for 36 h using a high-energy ball mill and then calcined at 310° C. for 12 h, accounting for 45.8 wt %.
[0099] The negative electrode active material, solid electrolyte and conductive carbon are put into a blender and mixed evenly, and different particles are dispersed by mechanical stirring. Then the polytetrafluoroethylene powder is mixed with the above powders and mixed evenly by a blender.
[0100] The mixed powder was placed in a high-speed mixer with paddles and mixed at 800 rpm for 20 minutes. The mixed material was then placed in a roller press and hot rolled at 200°C to form a self-supporting negative electrode sheet without a current collector, with a thickness of 70 microns. The above-mentioned electrode sheet was then rolled together with the negative current collector aluminum foil (thickness 20 microns) to form a complete solid-state battery negative electrode sheet with a peel strength of 31 mN / mm.
[0101] (3) Preparation of solid electrolyte membrane
[0102] Composition, based on the total mass of the solid electrolyte being 100wt%, polytetrafluoroethylene powder accounts for 7wt%, and the halide electrolyte Li 3 ScCl 6 , accounting for 93wt%.
[0103] The polytetrafluoroethylene powder and the solid electrolyte are mixed together and mixed evenly by a blender.
[0104] The mixed powder was placed in a high-speed mixer with paddles and mixed at 800 rpm for 20 minutes. The mixed material was then placed in a roller press and hot rolled at 80°C to form a self-supporting solid electrolyte membrane with a thickness of 80 microns.
[0105] (4) Dehydration
[0106] The solid-state battery positive electrode sheet was heated from room temperature to 170°C at a heating rate of 15°C / min, then kept at 170°C for dehydration for 2 minutes, and then cooled to 80°C at a rate of 12.5°C / min for standby use;
[0107] The solid electrolyte membrane and the solid battery negative electrode were heated from room temperature to 120°C at a heating rate of 15°C / min, then kept at 120°C for dehydration for 40 minutes, and then cooled to 80°C at a rate of 10°C / min for use.
[0108] (5) Assembly and packaging of components
[0109] The dehydrated solid-state battery positive electrode sheet, solid electrolyte membrane, and solid-state battery negative electrode sheet are rolled together, and the combined electrode sheets are packaged in an aluminum-plastic film packaging bag to prepare a solid-state battery.
[0110] Example 5
[0111] This embodiment provides a method for preparing a solid-state battery, comprising the following steps:
[0112] The positive electrode sheet, negative electrode sheet and solid electrolyte membrane are prepared according to the formulation and process methods of steps (1) to (3) of Example 4, and then the solid-state battery is assembled and packaged according to the method of step (5) of Example 4, and the packaged solid-state battery is dehydrated.
[0113] The solid-state battery was heated from room temperature to 120°C at a heating rate of 15°C / min, then kept at 120°C for dehydration for 20 minutes, and then cooled to room temperature at a rate of 15°C / min.
[0114] Example 6
[0115] The present embodiment provides a method for preparing a solid-state battery, which is basically the same as that of the first embodiment, except that the only difference is the dehydration treatment in step (4). The present embodiment only includes the dehydration treatment of the positive electrode sheet; that is, the positive electrode sheet of the solid-state battery is heated from room temperature to 100°C at a heating rate of 15°C / min, and then kept at 100°C for dehydration for 20 minutes, and then cooled to room temperature at a rate of 10°C / min for standby use.
[0116] Comparative Example 1
[0117] This comparative example provides a method for preparing a solid-state battery, which is basically prepared by the method of Example 1, except that the dehydration treatment step is omitted in this comparative example.
[0118] Comparative Example 2
[0119] This comparative example provides a method for preparing a solid-state battery, which is basically prepared by the method of Example 1, except for the dehydration step. The dehydration step of this comparative example is:
[0120] The solid-state battery positive electrode sheet is heated from room temperature to 80°C at a heating rate of 15°C / min, then kept at 80°C for dehydration for 10 minutes, and then cooled to room temperature at a rate of 10°C / min for standby use;
[0121] The solid electrolyte membrane and the solid battery negative electrode were heated from room temperature to 230°C at a heating rate of 10°C / min, then kept at 230°C for dehydration for 20 minutes, and then cooled to room temperature at a rate of 5°C / min for use.
[0122] Comparative Example 3
[0123] This comparative example provides a method for preparing a solid-state battery, which is basically prepared by the method of Example 1, except for the dehydration step. The dehydration step of this comparative example is:
[0124] The solid-state battery positive electrode sheet is heated from room temperature to 190°C at a heating rate of 15°C / min, then kept at 190°C for dehydration for 10 minutes, and then cooled to room temperature at a rate of 10°C / min for standby use;
[0125] The solid electrolyte membrane and the solid battery negative electrode were heated from room temperature to 230°C at a heating rate of 10°C / min, then kept at 230°C for dehydration for 20 minutes, and then cooled to room temperature at a rate of 5°C / min for use.
[0126] Comparative Example 4
[0127] This comparative example provides a method for preparing a solid-state battery, which is basically prepared by the method of Example 1, except for the dehydration step. The dehydration step of this comparative example is:
[0128] The solid-state battery positive electrode sheet is heated from room temperature to 150°C at a heating rate of 5°C / min, then kept at 150°C for dehydration for 10 minutes, and then cooled to room temperature at a rate of 10°C / min for standby use;
[0129] The solid electrolyte membrane and the solid battery negative electrode were heated from room temperature to 230°C at a heating rate of 10°C / min, then kept at 230°C for dehydration for 20 minutes, and then cooled to room temperature at a rate of 5°C / min for use.
[0130] Comparative Example 5
[0131] This comparative example provides a method for preparing a solid-state battery, which is basically prepared by the method of Example 1, except for the dehydration step. The dehydration step of this comparative example is:
[0132] The solid-state battery positive electrode sheet is heated from room temperature to 150°C at a heating rate of 15°C / min, then kept at 150°C for dehydration for 10 minutes, and then cooled to room temperature at a rate of 5°C / min for standby use;
[0133] The solid electrolyte membrane and the solid battery negative electrode were heated from room temperature to 230°C at a heating rate of 10°C / min, then kept at 230°C for dehydration for 20 minutes, and then cooled to room temperature at a rate of 5°C / min for use.
[0134] Experimental Example 1
[0135] After the solid-state batteries of each embodiment and comparative example were prepared, a batch of freshly prepared batteries were charged to 1.5V at a rate of 0.33C, and then discharged to 3V at 0.33C for cycle testing. Another batch of parallel samples were left standing at room temperature for 120 days and then subjected to cycle testing under the same test conditions to characterize the performance changes of the batteries after storage. The results are shown in the table below.
[0136] Table 1 Battery performance changes before and after storage
[0137]
[0138] As can be seen from the above table, the solid-state batteries obtained in each embodiment of the present invention have low performance changes before and after storage, and the specific capacity retention rate is significantly improved. Comparative Example 1 was not dehydrated, so after the battery was placed for 120 days, the specific capacity retention rate was only 76.5%, which was significantly lower than the retention rate of Example 1. The dehydration temperature of the positive electrode sheet in Comparative Example 2 is lower than the range specified in the present invention, and the free water and bound water cannot be effectively removed, so the specific capacity retention rate is reduced to 83.6% after standing for 120 days. The dehydration temperature of the positive electrode assembly in Comparative Example 3 is higher than the range specified in the present invention. The positive electrode active material is very easy to deoxidize at this temperature, causing structural collapse. The specific capacity of the solid phase is reduced from 203.2mAh / g to 172.2mAh / g compared to the freshly prepared battery in Example 1. Comparative Example 4 has a low heating rate and Comparative Example 5 has a low cooling rate, which prolongs the storage time of the positive electrode sheet at high temperature, thereby causing the positive electrode to lose oxygen more easily and causing performance degradation.
[0139] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for improving the storage life of a solid-state battery, characterized in that: The method for improving the storage life of a solid-state battery comprises a dehydration treatment step before assembly; The dehydration treatment before assembly includes heating the positive electrode sheet from room temperature to a predetermined temperature X1, keeping the temperature at the predetermined temperature X1 for T1 time, and cooling it to below 80°C; wherein, 100°C≤X1≤170°C, 1min≤T1≤10min, the heating rate of the positive electrode sheet is 15-20°C / min, and the cooling rate is 10-15°C / min; The dehydration step before assembly also includes: a step of dehydrating the negative electrode sheet and the solid electrolyte membrane, heating the negative electrode sheet and the solid electrolyte membrane from room temperature to a predetermined temperature X3, keeping the temperature at the predetermined temperature X3 for T3 time, and cooling to below 80°C; 120°C≤X3≤330°C, 10min≤T3≤40min; the heating rate of the negative electrode sheet and the solid electrolyte membrane is ≥10°C / min, and the cooling rate is ≥5°C / min.
2. A method for preparing a solid-state battery, characterized in that: The method for improving the storage life of a solid-state battery comprises the method of claim 1, and further comprises the preparation of a positive electrode sheet, the preparation of a negative electrode sheet and the preparation of a solid-state electrolyte membrane.
3. The method for preparing a solid-state battery according to claim 2, characterized in that: The preparation method of the positive electrode sheet comprises the following steps: mixing a binder, a positive electrode active material, a solid electrolyte and conductive carbon, rolling to obtain a positive electrode sheet, and pressing the positive electrode sheet with a current collector to obtain a positive electrode sheet; The preparation method of the negative electrode sheet comprises the following steps: mixing a binder, a negative electrode active material, a solid electrolyte and a conductive carbon, rolling and pressing to obtain a negative electrode sheet, and pressing the negative electrode sheet and a current collector to obtain a negative electrode sheet; The method for preparing the solid electrolyte membrane comprises the following steps: mixing the solid electrolyte with the binder, and rolling to obtain the solid electrolyte membrane.
4. The preparation method according to claim 3, characterized in that: The binder is selected from at least one of polyvinylidene fluoride, polyethylene oxide and polytetrafluoroethylene.
5. The preparation method according to claim 3 or 4, characterized in that: In the preparation method of the positive electrode sheet, the mass ratio of the binder, the positive electrode active material, the conductive carbon and the solid electrolyte is 0.2-5:50-90:0.05-4:1-50; and / or, in the preparation method of the negative electrode sheet, the mass ratio of the binder, the negative electrode active material, the solid electrolyte and the conductive carbon is 0.2-5:50-90:0.05-4:1-50; and / or, in the preparation of the solid electrolyte membrane, the mass ratio of the binder to the solid electrolyte is 0.1-10:90-99.9; and / or, the thickness of the positive electrode sheet is 50-120 microns; and / or, the thickness of the solid electrolyte membrane is 20-200 microns; and / or, the thickness of the negative electrode sheet is 60-170 microns.
6. The method for preparing a solid-state battery according to claim 5, characterized in that: In the preparation of the positive electrode sheet and / or the preparation of the negative electrode sheet and / or the preparation of the electrolyte membrane, the mixing method is at least one of grinding, ball milling, stirring, oscillation and ultrasound; and / or the rolling temperature is 40-220°C.
7. The method for preparing a solid-state battery according to claim 2 or 3, characterized in that: The negative electrode active material is selected from at least one of graphite, silicon dioxide, silicon, lithium carbonate, and lithium titanate; and / or the solid electrolyte is selected from at least one of sulfide electrolytes, halogen electrolytes, and oxide electrolytes; and / or the positive electrode active material is selected from at least one of nickel cobalt manganese materials, nickel manganese lithium oxide materials, nickel lithium oxide materials, lithium cobalt oxide materials, nickel cobalt lithium oxide materials, and nickel manganese cobalt lithium oxide materials; and / or the conductive carbon is selected from at least one of carbon black, acetylene black, carbon nanotubes, and graphene.
8. A solid-state battery prepared by the preparation method described in any one of claims 2 to 7.
Citation Information
Patent Citations
Preparation method of all-solid-state battery, and all-solid-state battery
CN112928337A
Solid-state battery
JP2009193729A
Storage method and storage device of solid electrolyte, and manufacturing method of all solid state battery
JP2013201111A
Manufacturing method of sulfide all-solid battery
JP2014216217A
Method for manufacturing all-solid battery
JP2017050209A
